Neisseria gonorrhoeae culture growth rates from asymptomatic individuals with a positive nucleic acid amplification test. (5th August 2022) - Nadal‐Baron, P.; Salmerón, P.; García, J. N.; Trejo‐Zahinos, J.; Sulleiro, E.; Lopez, L.; Jiménez de Egea, C.; Zarzuela, F.; Ruiz, E.; Blanco‐Grau, A.; Llinas, M.; Barberá, M. J.; et al.
Abstract: Gonorrhoea infections are frequently diagnosed at extragenital locations in asymptomatic individuals and are historically related to poor recovery in culture, which hinders antimicrobial susceptibility testing. The aim of this study was to evaluate recovery rates of Neisseria gonorrhoeae by culture among asymptomatic individuals who tested positive by nucleic acid amplification tests between 2018 and 2019 in Barcelona (Spain). In total, 10 396 individuals were tested for N. gonorrhoeae on first‐void urine, rectal, pharyngeal and/or vaginal swabs depending on sexual behaviour. Overall infection prevalence was 5·5% (95% confidence interval [CI] 5·0–5·9). Seven hundred and ten samples were positive corresponding to 567 individuals. The most common site of infection was the pharynx (71·3%), followed by rectum (23·1%) and genitals (4·7%) ( P  < 0·0001). The N. gonorrhoeae recovery rate in culture, time from positive screening to culture specimen and inoculation delay were calculated. Recovery rate was 21·7% in pharynx, 66·9% in rectum and 37·0% in genitals (25·0% vagina, 71·4% urethra) ( P  < 0·0001). Median culture collection time was 1 [0; 3] days, and median inoculation delay was 5·01 [4·99–7·99] h, with no impact on N. gonorrhoeae recovery, P  = 0·8367 and P  = 0·7670, respectively. Despite efforts towards optimizing pre‐analytical conditions, the N. gonorrhoeae recovery rate in asymptomatic individuals is unacceptably low (especially for pharynx), representing a problem for monitoring antimicrobial‐resistant infections. Abstract : Significance and Impact of the Study: Neisseria gonorrhoeae culture remains indispensable to monitor antimicrobial‐resistant infections. This standardized study shows that the infection location of gonorrhoea directly impacts on culture recovery. We report that recovery of N. gonorrhoeae from extragenital sites (especially pharynx) is unacceptably low and that reducing pre‐analytical times is not sufficient to optimize culture recovery.